2023
DOI: 10.1063/5.0144937
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic evaluation of cascade flow with actual geometric uncertainties using an adaptive sparse arbitrary polynomial chaos expansion

Abstract: In the paper, an adaptive sparse arbitrary polynomial chaos expansion (PCE) is first proposed to quantify the performance impact of realistic multi-dimensional manufacturing uncertainties. The Stieltjes algorithm is employed to generate the PCE basis functions concerning geometric variations with arbitrary distributions. The basis-adaptive Bayesian compressive sensing algorithm is introduced to retain a small number of significant PCE basis functions, requiring fewer model training samples while preserving fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Dow and Wang (2014, 2015) emphasized that the impact of geometric deviations on compressor design performance should not be overlooked in shape robust design. Guo et al (2022, 2023) investigated the effects of blade profile deviation and stagger angle deviation on the performance of compressor cascades. They found that thickness deviations in the leading edge and the front half of the suction surface of the blades have a significant impact on cascade performance.…”
Section: Introductionmentioning
confidence: 99%
“…Dow and Wang (2014, 2015) emphasized that the impact of geometric deviations on compressor design performance should not be overlooked in shape robust design. Guo et al (2022, 2023) investigated the effects of blade profile deviation and stagger angle deviation on the performance of compressor cascades. They found that thickness deviations in the leading edge and the front half of the suction surface of the blades have a significant impact on cascade performance.…”
Section: Introductionmentioning
confidence: 99%